Advancing human-use experience for real-world evidence for the registration of traditional Chinese medicine products in China - Mingge Xia; Yan Xue; Luwei Zhu; Xianwen Chen; Carolina Oi Lam Ung; Sheng Han; Yunfeng Lai; Hao Hu (BMC Complementary Medicine and Therapies)
Abstract Background The registration application of traditional Chinese medicine (TCM) products as new drugs often meets the challenges of lacking clinical evidence from randomized controlled trials (RCT). In recent years, China has introduced a new evidence system for the review and approval of TCM products, which proposed using human-use experience (HUE) for real-world evidence (RWE) to support the safety and effectiveness of TCM. Purpose This study aimed to comprehensively analyse the regulatory concerns, policy guidances, and approved cases of using HUE to register TCM products. Methods Literature search and thematic analysis were conducted to identify and synthesize the regulatory concerns. A documentary analysis of policy guidances was employed to present the evolving regulatory framework for incorporating HUE into TCM registration in China. Case studies of approved TCM products using HUE to support registration were conducted, and the study design, study population, and postmarked requirements of these cases were analyzed. Results Four main themes and 12 sub-themes regarding regulatory concerns of applying HUE in the registration of TCM products were identified. The 4 main themes are HUE quality, HUE applicability, HUE governance, and HUE regulation. Six policy documents and seven technical guidances were released to facilitate the application of HUE in TCM registration, founding a practical regulatory framework for TCM product registration. In China, six cases that employed HUE to support registration were approved. Of these, five cases utilized HUE to support direct registration, while one utilized HUE to lay the foundation for subsequent phase III clinical trial. Regarding study design and data types, retrospective observational studies were the predominant approach and electronic health records from the hospital information systems were the most commonly used data source. Among the five cases of direct registration, three relied solely on retrospective observational studies, while two conducted small-sample prospective studies in conjunction with retrospective observational studies. Conclusion HUE can be advanced to generate RWE for the safety and effectiveness of TCM products, which provides potential support for registering new TCM products. Leveraging HUE for registration can shorten research and development period, reduce development costs, and promote innovation, ultimately driving the growth of the TCM industry. However, several challenges remain in using HUE to support the registration of TCM products in China, including difficulties in data accessibility, lack of standardized protocols for HUE collection and reporting, and obstacles in transforming TCM preparations from hospitals into new TCM products using HUE. Furthermore, ensuring high-quality HUE requires future attention to data applicability, data infrastructure, and research design.